ROBO SOCCER SEBAGAI MEDIA EDUKASI PENGENALAN TEKNOLOGI ROBOTIKA PADA SISWA DI SEKOLAH MENENGAH ATAS - Yohanes Calvinus; Endah Setyaningsih (Jurnal Bakti Masyarakat Indonesia, 2020)
Robotics technology has now become a technological requirement for all students, both at the elementary school, junior high school and high school level. In fact in some private and public schools the need for education in robotics technology is only a discourse and cannot be realized properly. Many of these schools are trying to work with several agencies providing private education services for robotics. The lack of human resources and knowledge about robotics among high school students has caused these students to not know or lack in participating in the event that should have been the driving force behind the industrial revolution 4.0 about automation and robotics. Even in Jakarta there are not many competitions in the form of robotics competitions that can be participated by high school students. The community engagement team at Tarumanagara University conducted workshops and robot competitions in the form of robo soccer, which also functioned as a media for robotics technology education for high school students. High school students are introduced to robot components in the form of electrical and mechanical components, also about programming. Students are also asked to assemble these components and the results are in the form of robo soccer. These high school students are very happy and enthusiastic about this activity, because curiosity about robots can be achieved. Students from various schools are also active in participating in the Edurobocup Contest organized by the Electrical Engineering study program at Tarumanagara University. It is hoped that this activity can be routinely carried out every year, so that robotics technology can be known while students are still in high school.ABSTRAK:Teknologi Robotika saat ini telah menjadi suatu kebutuhan teknologi bagi seluruh pelajar, baik tingkat Sekolah Dasar, Sekolah Menengah Pertama, maupun Sekolah Menengah Atas. Kenyataannya di beberapa sekolah swasta dan negeri kebutuhan pendidikan akan teknologi robotika ini hanya menjadi wacana dan belum dapat terealisasi dengan baik. Banyak sekolah-sekolah tersebut berusaha bekerjasama dengan beberapa instansi penyedia jasa pendidikan swasta untuk robotika. Minimnya sumber daya manusia dan pengetahuan tentang robotika di kalangan siswa SMA menyebabkan siswa tersebut tidak tahu ataupun kurang dalam mengikuti ajang yang seharusnya menjadi pendorong kemajuan revolusi industri 4.0 tentang otomasi dan robotika. Bahkan di Jakarta belum banyak kompetisi berupa perlombaan robotika yang dapat diikuti oleh siswa SMA. Tim pengabdian kepada masyarakat Universitas Tarumanagara melakukan workshop dan lomba robot berupa robo soccer, yang sekaligus difungsikan sebagai media edukasi teknologi robotika bagi siswa SMA. Siswa SMA dikenalkan tentang komponen robot yang berupa komponen elektrik dan mekanik, juga tentang pemrograman. Siswa juga diminta merakit komponen-komponen tersebut dan hasilnya berupa robo soccer. Siswa SMA ini sangat senang dan antusias mengikuti kegiatan ini, karena keingintahuan tentang robot dapat tercapai. Siswa dari berbagai sekolah juga aktif dalam mengikuti Lomba Edurobocup yang diselenggarakan oleh program studi teknik elektro Universitas Tarumanagara. Diharapkan kegiatan ini dapat rutin dilakukan tiap tahun, sehingga teknologi robotika dapat dikenal saat siswa masih di SMA